Lower waist circumference in mildly‐stunted adolescents is associated with elevated insulin concentration - Ana Paula Grotti Clemente; Carla Danusa da Luz Santos; Vinicius J.B. Martins; Maria Paula Albuquerque; Mariana B. Fachim; Ana Lydia Sawaya (Brazilian Society of Pediatrics, 2014)
Objective: Augmented waist circumference (WC) is associated with non‐communicable diseases and could represent a valuable marker in screening for metabolic dysfunctions in subjects with insufficient linear growth. The objective of the present study was to determine whether biochemical and hemodynamic parameters and waist circumference vary between mildly‐stunted and non‐stunted adolescents from impoverished communities of São Paulo, Brazil. Methods: The cross‐sectional study involved 206 subjects, aged between 9 and 19 years and living in impoverished areas of São Paulo, Brazil. The sample population was divided according to height‐for‐age Z‐score (HAZ) into stunted (-1 > HAZ ≥ -2) and non‐stunted (HAZ ≥ -1) groups, and was sub‐divided according to gender. Logistic regression analysis was employed to compare individuals with elevated (> 75th percentile) insulin concentrations. The receiver operating characteristic curves were constructed to determine WC cut‐off points that could be used to identify stunted and non‐stunted individuals with elevated insulin concentrations. Results: WC cut‐off points of 58.25 cm and 67.2 cm allowed for correct classification of 90.7% of stunted and 88.7% of non‐stunted individuals in the studied population. While the sensitivity of the model was high for stunted and non‐stunted subjects (98.8% and 97.2%, respectively), the specificity was modest (57.1% and 41.2%, respectively). Conclusion: The results presented herein suggest that an increase in plasma insulin is one of the primary metabolic modifications in stunted individuals, and that this alteration could be identified at a lower WC cut‐off point than in non‐stunted counterparts.